Anger and inequality breeding ‘terrorists’ - Abd Razak, Dzulkifli (2006)
TWO official reports on the 2005 July bombing on the London transport system which killed more than 50 people were released last week. One of the youths left a video claiming responsibility, backed up by other videotapes implicating their involvement. The event was the worst attack of its kind in British history. Three of them were known in some form by the British authorities but the security service failed to follow up, said one of the reports published by the Intelligence and Security Committee of Parliament which reports directly to the Prime Minister. The other is a more "narrative" 41page report from the Home Office. Many questions were left unanswered, including the failure to fully understand the threat from homegrown suicide bombers.